Holographic Optical Elements for Augmented Reality: Principles, Present Status, and Future Perspectives - Xiong, Jianghao; Yin, Kun; Li, Kun; Wu, Shin-Tson (Advanced photonics research, 2021)
Holographic optical elements (HOEs) exhibit several unique properties in arbitrary wavefront recording and extraction. Versatile recording mechanisms and material availabilities further expand their design flexibilities. Augmented reality (AR) displays are emerging and transforming daily life. Applications of HOEs in AR have harvested numerous fruitful evolutionary and revolutionary progresses. Herein, the basic operation principles of HOEs are elucidated, recent advances in AR systems are reviewed, and their future perspectives are discussed. Herein, the underlying physics of holographic optical element (HOE) formation are introduced first and their unique optical properties and functionalities are described. Next, the applications of HOEs in several augmented reality (AR) display systems are briefly reviewed and their pros and cons are analyzed. Finally, some perspectives are cast on future developments of HOEs for AR displays.